Drought adaptation and economic impacts on smallholder rice farmers - Raghu, Prabhakaran T.; Chellattan Veetil, Prakashan; Das, Sukanya (Elsevier BV, 2025)
Frequent droughts pose a significant threat to sustainable agricultural development, particularly in vulnerable regions. This study investigated the adoption and impacts of Sahbhagi Dhan, a drought-tolerant rice variety, among marginal and tribal farmers who heavily relied on rice farming for their livelihoods. Based on household survey data from 2710 households collected in 2017, the findings revealed that 37.7 % of the sample households adopted Sahbhagi Dhan between 2013 and 2016. Farmers who adopted this variety achieved higher yields and incomes compared to those cultivating other rice varieties. Notably, during drought years, yields losses of Sahbhagi Dhan were limited to only 13.6 % compared to yields under normal conditions, demonstrating its resilience. The adoption of Sahbhagi Dhan also contributed to a significant reduction in rice-fallow areas by improving land use efficiency during challenging climatic conditions. However, seed unavailability emerged as a major barrier, leading to the discontinuation of cultivation among farmers. To enhance food security and build drought resilience, it is essential to ensure the availability of climate-resilient varieties like Sahbhagi Dhan. Additionally, providing timely and relevant information can encourage adoption among non-adopters and support farmers who discontinued its use.